Effects of Peer Tutoring on the Academic Achievement of Students in the Subject of Biology at Secondary Level - Irfan Ullah; Rabia Tabassum; Muhammad Kaleem (MDPI AG, 2018)
The present study is aimed at analyzing the effects of peer tutoring on the academic achievement of students in the subject of biology at secondary level. The objectives of the study were: (1) To find out the effects of peer tutoring on the academic achievement of students in the subject of biology; and (2) To examine the effects of peer tutoring with respect to knowledge, comprehension and application levels in cognitive domain of Bloom Taxonomy. All 433,405 male students at secondary level of 10th grade of Khyber Pakhtunkhwa were the population of the study. Forty students were taken as the sample of the study from the Allied National Software Institute (ANSI) Mardan. The Posttest-Only Equivalent Group Design was used. The data collected from pretest and posttest were analyzed through an independent sample t-test. It was found that the mean score of the experimental group was significantly better than that of the control group. It was concluded that peer tutoring enhanced the academic achievement of students in the experimental group significantly as compared to the control group; hence, it was an effective method of instruction for teaching biology at secondary level. It was suggested that peer tutoring may be incorporated along with other teaching methodologies for the subject of biology and it may be given due consideration in all teacher education practices in the country.